2013
DOI: 10.1016/j.ijid.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A family cluster of Middle East Respiratory Syndrome Coronavirus infections related to a likely unrecognized asymptomatic or mild case

Abstract: MERS-CoV acquisition from unrecognized mild or asymptomatic cases may be a more important contributor to ongoing transmission than previously appreciated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
179
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(189 citation statements)
references
References 15 publications
9
179
0
1
Order By: Relevance
“…Similarly, the absence of transmission to the community contact may have been due to the case-patient's lack of respiratory symptoms during the 2 meetings. The absence of transmission to household and community contacts in this investigation is similar to that seen in contact investigations of several other patients with MERS (11-13); however, in other settings, transmission to household members who provided care to persons with MERS-CoV infection have been reported, and household clusters have been documented (3)(4)(5)(6)(7)16).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similarly, the absence of transmission to the community contact may have been due to the case-patient's lack of respiratory symptoms during the 2 meetings. The absence of transmission to household and community contacts in this investigation is similar to that seen in contact investigations of several other patients with MERS (11-13); however, in other settings, transmission to household members who provided care to persons with MERS-CoV infection have been reported, and household clusters have been documented (3)(4)(5)(6)(7)16).…”
Section: Discussionsupporting
confidence: 82%
“…Clusters of MERS-CoV infection have occurred within extended families, households, and healthcare settings (3)(4)(5)(6). Contact investigations around imported cases in the United Kingdom, France, and Tunisia identified cases among household and healthcare contacts, suggesting person-to-person transmission (7)(8)(9).…”
mentioning
confidence: 99%
“…While the source or reservoir of MERS-CoV is unknown, the disease is transmitted from person to person, for example by close contacts or in healthcare facilities [17][18][19][20][21][22][23][24]. Based on information related to the first 77 cases, the basic reproduction number of the infection (R0) was estimated to be 0.69 (95% CI 0.50-0.92) at the time [25], indicating a low pandemic potential [26].…”
Section: Human-to-human Transmissionmentioning
confidence: 99%
“…7 Moreover, it was reported that unrecognized, asymptomatic patients transferred MERS-CoV to their family or close contacts. 9 All these factors were alarming and potentially distressing for the hospital staff who worked during the outbreak.…”
mentioning
confidence: 99%